2015
DOI: 10.1038/srep08133
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic Astrocyte-Derived Neurotrophic Factor Is Involved in Inflammation by Negatively Regulating the NF-κB Pathway

Abstract: Inflammation can cause endoplasmic reticulum (ER) stress and therefore activates the unfolded protein response (UPR). ER stress and the consequent UPR have the potential to activate NF-κB. However, the factors mediating the crosstalk between ER stress and the NF-κB pathway remain unclear. Here, we determined that ER stress inducible protein Mesencephalic Astrocyte-derived Neurotrophic Factor (MANF) was up-regulated in autoimmune diseases and inflammatory disease models. Inflammation caused MANF to relocalize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 42 publications
(54 reference statements)
3
99
0
Order By: Relevance
“…MANF can also repress proliferation of inflammatory fibroblast-like synoviocytes in a rodent methylated bovine serum albumin-induced arthritis model 29 . Furthermore, MANF can alleviate oxygen–glucose deprivation-induced cell damage and inflammation in rat primary astrocytes 61 , as well as suppress lipopolysaccharide-induced inflammatory response in neural stem cells 62 .…”
Section: Manf Functions (Table 1) and Underlying Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…MANF can also repress proliferation of inflammatory fibroblast-like synoviocytes in a rodent methylated bovine serum albumin-induced arthritis model 29 . Furthermore, MANF can alleviate oxygen–glucose deprivation-induced cell damage and inflammation in rat primary astrocytes 61 , as well as suppress lipopolysaccharide-induced inflammatory response in neural stem cells 62 .…”
Section: Manf Functions (Table 1) and Underlying Mechanismsmentioning
confidence: 99%
“…It has been shown that the small C-terminal domain is responsible for the intracellular protection against the Bax-dependent apoptosis in the sympathetic superior cervical ganglion (SCG) neurons 27 . It has also been shown that the C-terminal SAP-like domain of MANF interacts with the DNA binding domain of NF-κB p65 subunit after translocation of MANF into nucleus under inflammation and ER stress, which negatively regulates NF-κB signaling 29 . MANF contains eight conserved cysteines that form four intramolecular disulfide bonds including two in CXXC sequences 28 .…”
Section: Manf Structurementioning
confidence: 99%
See 3 more Smart Citations